Chief Editor's Voice - Jha, Prof. Dr. Ashok Kumar (Dristikon: A Multidisciplinary Journal, 2021)
The RMC of the campus feels much pleasure to publish the annual multi-disciplinary peer reviewed research journal DRISTIKON as vol. 11(1). The journal and the articles published in it are clear evidence and fulfill the requirements laid down by UGC, Nepal, Tribhuvan University Service Commission, APA 7th ed. and other platforms. The journal is designed to serve as an outlet for an intellectual forum for the communication of intellectual ideas among professionals and other social scientists in relevant areas in general and with special reference to Nepal. The board welcomes all the professionals, researchers and all those interested to publish their research findings with significant contribution to society, education sector and international platform. Authors are also encouraged to submit papers which are related to current international, national or local issues. Almost all the scholarly and research articles published in the journal undergo the editorial peer review process prior to publication to fulfill the requirements of peer review process guided by UGC, Nepal and international standard. The goal of the peer review process is to ensure that the valid article is accepted, the messy article cleaned up, and the invalid article rejected. The board of editors has accepted the reviewer’s recommendations. All the articles submitted for publication are subjected to rigorous double blinded peer review to ensure its quality before it gets published. Manuscripts submitted to this journal must not have been published or accepted for publication or submitted for publication elsewhere. The journal strictly follows guidelines of APA 7th ed. as well as strongly opposes plagiarized contents without proper citation. Following the necessary corrections and additions resulting from the review process the twenty accepted papers were included into the issue covering the specific areas of Nepali, English, Political Science, Science and Management. The cooperation extended by scholars and institutions in publishing this journal is highly appreciated. The opinions expressed in the articles are the author’s own and do not reflect the view of either the publisher or the editorial board. All manuscripts once published becomes the property of the publisher. We hope that inspiration and encouragement from the readers will continue to keep the ‘Dristikon’ alive and develop. We are also looking forward to receiving your comments and suggestions for further improvement in the future. We are grateful to the peer reviewers for their valuable comments and suggestions. The editorial board heartily thanks all the writers who have contributed research articles. We would also like to give special thanks to the campus chief Mr. Damodar Bhandari for his constant support in terms of finance and administration for the publication of this journal.